The Politics and Poetics of Cicero's Brutus : The Invention of Literary History - Van den Berg, Christopher Sean (University of Cambridge ESOL Examinations, 2021)
Cicero's dialogue on oratory responded to the political crisis of Julius Caesar but ultimately invented 'modern' literary history